Accumulation of dry mass and macronutrients by Glycine max and solanum Americanum plants Acúmulo de massa seca e de macronutrientes por plantas de Glycine max e Solanum Americanum - Bianco S. (2012)
Soybean is one of the main crops in Brazil, but its productivity is very affected by weed competition. Two experiments were carried out in Jaboticabal, SP, Brazil, under greenhouse conditions to determine the accumulation and distribution of dry mass and macronutrients in soybean cv. BR-16, from October 2000 to February 2001, and Solanum americanum plants, from January to May 1995. Plants were grown in seven liter pots filled with river sand substrate and were daily irrigated with nutrient solution. The treatments were constituted by the times of samplings carried out at 14 day intervals, starting 21 days after emergence (DAE). Soybean evaluation was extended to 161 DAE, while S. americanum was extended to 119 DAE. The point of maximum theoretical accumulation of dry mass in soybean occurred at 104 DAE (35.00 g per plant) while for S. americanum, it occurred at 143 DAE (179.62 g per plant). From emergence until 49 and 63 DAE, leaves showed higher participation in dry mass accumulation of soybean and S. americanum, respectively. After these periods, an inversion could be observed, with leaves being surpassed by stems for the weeds, and by stems and later, by reproductive structures, for the crop. Macronutrient uptake rate reached higher values between 69 to 87 DAE for soybean and between 105 to 119 DAE for S. americanum. Considering the mean inflexion point values observed in soybean crop, at 75 DAE, it can be evidenced that one soybean plant theoretically accumulated 23.90 g of dry mass, 564.40 mg of N, 7.10 mg of P, 490.80 mg of K, 487.00 mg of Ca, 156.60 mg of Mg and 36.00 mg of S, while one S. americanum plant theoretically accumulated 33.75 g of dry mass, 875.96 mg of N, 88.46 mg of P, 983.54 mg of K, 647.60 mg of Ca, 100.93 mg of Mg, and 42.15 mg of S.